Analisis Sentimen Kepuasan Pengguna OYO DiPlaystore Dengan Multinoial Naive Bayes dan Chi-square - Aziz, Rizky; Tresna Maulana Fahrudin; Wahyu Syaifullah Jauharis Saputra (Unversitas Muhammadiyah Riau, 2024)
ABSTRACKOpinions play a crucial role in everyday life, significantly influencing human behavior and decisions. Especially in the context of business and organizations, consumer opinions about products and services are highly valuable. This study focuses on analyzing the sentiment of OYO application reviews on the Google Play Store, with the goal of classifying reviews as either positive or negative. OYO Hotels & Homes, a startup company in the accommodation sector originating from India, has achieved remarkable success with revenues reaching US951 million in fiscal year 2019. The primary classification method used is Multinomial Naïve Bayes, which is an approach in supervised learning, along with Chi-Square feature selection to explore correlations between factors influencing user satisfaction. The research process includes data collection of reviews, preprocessing, labeling, and data splitting. Subsequently, TF-IDF weighting and Chi-Square feature selection are performed. The results of sentiment analysis indicate a dominance of positive reviews, reflecting user satisfaction with OYO services. The classification process uses the Multinomial Naïve Bayes algorithm, with an accuracy rate of 85.5% without feature selection, increasing to 87.00% with Chi-Square feature selection. These results demonstrate the effectiveness of the Multinomial Naïve Bayes algorithm and the importance of feature selection in sentiment analysis. Through a deeper understanding of user sentiment, companies can enhance service quality and respond to feedback more effectively, ensuring optimal customer satisfaction. This research has broad implications for sentiment analysis and the use of statistical methods to address complex issues in the technology industry. Keywords: Sentiment Analysis, OYO Application, Google Playstore, Multinomial Naïve Bayes, Chi-Square Feature Selection. Abstrak Opini memainkan peran krusial dalam kehidupan sehari-hari, memengaruhi perilaku dan keputusan manusia secara signifikan. Terutama dalam konteks bisnis dan organisasi, pendapat konsumen tentang produk dan layanan sangatlah berharga. Penelitian ini berfokus pada analisis sentimen ulasan aplikasi OYO di Google Playstore, dengan tujuan mengklasifikasikan ulasan menjadi positif atau negatif. OYO Hotels & Homes, sebuah perusahaan startup di sektor akomodasi yang berasal dari India, telah mencapai kesuksesan luar biasa dengan pendapatan mencapai US951 juta pada tahun fiskal 2019. Metode klasifikasi utama yang digunakan adalah Multinomial Naïve Bayes, yang merupakan pendekatan dalam pembelajaran terawasi dan seleksi fitur Chi-Square untuk mengeksplorasi korelasi antara faktor-faktor yang memengaruhi kepuasan pengguna. Proses penelitian meliputi pengumpulan data ulasan, preprocessing, labeling, dan pembagian data. Selajutnya dilakukan pembobotan TF-IDF dan seleksi fitur Chi-Square. Hasil analisis sentimen memperlihatkan dominasi ulasan positif, menunjukkan kepuasan pengguna terhadap layanan OYO. Proses klasifikasi menggunakan algoritma Multinomial Naïve Bayes, dengan hasil akurasi model tanpa seleksi fitur sebesar 85.5%, meningkat menjadi 87.00% dengan seleksi fitur Chi-Square. Hasil ini menunjukkan efektivitas algoritma Multinomial Naïve Bayes dan pentingnya seleksi fitur dalam analisis sentimen. Melalui pemahaman yang lebih dalam terhadap sentimen pengguna, perusahaan dapat meningkatkan kualitas layanan dan merespons umpan balik dengan lebih baik, memastikan kepuasan pelanggan yang optimal. Penelitian ini memiliki implikasi luas dalam analisis sentimen dan penggunaan metode statistik untuk mengatasi masalah kompleks dalam industri teknologi.